The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0028-3932(97)00111-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical plasticity in perceptual learning demonstrated by transcranial magnetic stimulation

Abstract: Performance on a wide range of perceptual tasks improves with practice. Most accounts of perceptual learning are concerned with changes in neuronal sensitivity or changes in the way a stimulus is represented. Another possibility is that different areas of the brain are involved in performing a task during and after learning it. Here, we demonstrate that the right parietal cortex is involved in novel but not learned visual conjunction search. We observed that single pulse transcranial magnetic stimulation (TMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…The early decrease in activation along the IPS (between sessions 1 and 3) precedes the later increase in activation in the postcentral gyrus (between sessions 3 and 5). This shows that the latter is not immediately contingent on the former; it may indicate that learning in the object matching task occurred in two steps: an initial step in which a perceptual representation of the object pair was generated, reducing visual attentional demands, and a second step in which the perceptual object representation was associated with the appropriate response 4 . According to such a sequential model, fast learners may have begun responserelated learning even before session 3, whereas slow learners may reach this transition only after session 3.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The early decrease in activation along the IPS (between sessions 1 and 3) precedes the later increase in activation in the postcentral gyrus (between sessions 3 and 5). This shows that the latter is not immediately contingent on the former; it may indicate that learning in the object matching task occurred in two steps: an initial step in which a perceptual representation of the object pair was generated, reducing visual attentional demands, and a second step in which the perceptual object representation was associated with the appropriate response 4 . According to such a sequential model, fast learners may have begun responserelated learning even before session 3, whereas slow learners may reach this transition only after session 3.…”
mentioning
confidence: 94%
“…In particular, the cortex along the horizontal segment 5 of the intraparietal sulcus (IPS) is involved in shifting attention in space 6,7 or between feature dimensions 8 . Disruption of attentionally demanding visual search by parietal TMS disappears when search becomes automatic after learning 4 . Similarly, activation in the superior parietal lobule decreases after skill learning 9 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies showed that training can speed conjunction search (e.g. Carrasco, Ponte, Rechea & Sampedro, 1998; Frank et al, 2014; Su et al, 2014; Walsh, Ashbridge & Cowey, 1998), which requires not only detecting and discriminating features, but also binding them together. But it is unknown whether the improvements observed in feature-conjunction search reflect improvement in feature representation ( feature-learning ), feature binding ( binding-learning ) or both.…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS), introduced by Barker et al (1985; for review, see: George et al, 2003;Nollet et al, 2003;Reid, 2003;Siebner & Rothwell, 2003) and applied mostly in studies of motor cortex (Ganis et al, 2000;Garry et al, 2004) and for the treatment of depression and other brain disorders (Wassermann & Lisanby, 2001) is a technique increasingly used as a noninvasive tool in cognitive neuroscience (Jahanshahi & Rothwell, 2000;Walsh & Cowey, 2000;Bailey et al, 2001;Rossi & Rossini, 2004). In numerous human studies, TMS has been applied to investigate brain mechanisms of learning and memory, particularly in studies using working memory tasks (Duzel et al, 1996;Hong et al, 2000;Mull & Seyal, 2001;Oliveri et al, 2001;Harris et al, 2002;Mottaghy et al, 2002Mottaghy et al, , 2003Herwig et al, 2003;Nyffeler et al, 2004) but also in various other memory tasks (Walsh et al, 1998;Stewart et al, 1999;Hadland et al, 2001;Sandrini et al, 2003).…”
Section: Introductionmentioning
confidence: 99%